The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1108/eb060721
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Audit Expectations Gap in Singapore

Abstract: This study adds to the literature on the audit expectations gap (AEG) by examining the extent to which lower levels of user cognisance of the role, objectives, and limitations of an audit are associated with unreasonable audit expectations and perceptions. Cognisance is proxied by respondents' demographic characteristics including profession, work experience, university qualification, age, and gender. Respondents include 130 Singaporean auditors, prepares, and users of audited financial reports. Results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…The studies include those of Lee (1970), Humphrey et al. (1993) and Porter and Gowthorpe (2004) in the UK; Beck (1973) and Monroe and Woodliff (1994) in Australia; Porter (1993) and Porter and Gowthorpe (2004) in NZ; Leung and Chau (2001) in Hong Kong; De Martinis et al . (2000) and Best et al .…”
Section: Prior Research Investigating the Audit Expectation Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies include those of Lee (1970), Humphrey et al. (1993) and Porter and Gowthorpe (2004) in the UK; Beck (1973) and Monroe and Woodliff (1994) in Australia; Porter (1993) and Porter and Gowthorpe (2004) in NZ; Leung and Chau (2001) in Hong Kong; De Martinis et al . (2000) and Best et al .…”
Section: Prior Research Investigating the Audit Expectation Gapmentioning
confidence: 99%
“…The audit expectation gap has been the subject of research over an extended period and in a variety of jurisdictional and cultural contexts. The studies include those of Lee (1970), Humphrey et al (1993) and Porter and Gowthorpe (2004) in the UK; Beck (1973) and Monroe and Woodliff (1994) in Australia; Porter (1993) and Porter and Gowthorpe (2004) in NZ; Leung and Chau (2001) in Hong Kong;De Martinis et al (2000) and Best et al (2001) in Singapore; Lin and Chen (2004) in the People's Republic of China; Fadzly and Ahmed (2004) and Lee et al (2007) in Malaysia; Gloeck and de Jager (1993) in South Africa; Alleyne and Howard (2005) in Barbados; Garcia-Benau et al (1993) in Spain; Troberg and Viitanen (1999) in Finland; Haniffa and Hudaib (2007) in Saudi Arabia; Dixon et al (2006) in Egypt;and Sidani (2007) in Lebanon. Most of the studies involve surveys designed to ascertain the opinions of different interest groups about the role and/or responsibilities of financial statement auditors in the country concerned.…”
Section: Prior Research Investigating the Audit Expectation Gapmentioning
confidence: 99%
“…Further, Sikka et al (1992) contend that the 'expectation gap' is an outcome of the contradiction of minimum government regulation and the profession's self-regulation, especially, the profession's over-protection of self-interest, which has widened the 'expectation gap', this statement is also supported by Giacomino (1994);and Chandler and Edwards (1996). Martinis et al (2000) view audit expectation gap by examining the extent to which lower levels of user cognizance of the role, objectives and limitations of an audit are associated with unreasonable audit expectations and perceptions. It found that the audit expectation gap prevailed where respondents had relatively little business work experience and no university qualifi cations.…”
Section: The Rising Gapmentioning
confidence: 79%
“…Further, Sikka et al (1992) contend that the 'expectation gap' is an outcome of the contradiction of minimum government regulation and the profession's selfregulation, especially, the profession's over-protection of self-interest, which has widened the 'expectation gap', this statement is also supported by Giacomino (1994) and Chandler and Edwards (1996). Martinis et al (2000) views audit expectation gap by examining the extent to which lower levels of user cognizance of the role, objectives and limitations of an audit are associated with unreasonable audit expectations and perceptions. It was found that the audit expectation gap prevailed where respondents had relatively little business work experience and no university qualifications.…”
Section: The Rising Gapmentioning
confidence: 99%
“…In addition, there was evidence that investors believed that auditors had some responsibility for ensuring an entity of sound internal controls. Martinis et al (2000) made an examination of the audit expectation gap in Singapore. The main objectives of their study were (i) to examine the extent to which lower levels of user cognizance of the role, objectives and limitations of an audit were associated with unreasonable audit expectations and perceptions, and (ii) to identify the extent of the gap with regard to the expectations and perceptions about the duties and responsibilities of auditors, fraud prevention and detection.…”
Section: Review Of Literaturementioning
confidence: 99%